The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1098/rstb.1991.0109
|View full text |Cite
|
Sign up to set email alerts
|

Hominoid dietary evolution

Abstract: During the later Palaeocene and early Miocene, catarrhine primates and the evolving hominoids had adaptations for frugivorous diets, with the emphasis on soft foods. Early in the middle Miocene the hominoids underwent a major shift, both in morphology and in habitat, with the morphology characterized by thickened enamel on the molars, enlarged incisors and massive jaws. The diet indicated by this morphology is interpreted as still mainly frugivorous but with changed emphasis, possibly towards harder objects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…(c) Left, horizontal section after the entire volume data set of (b) was rotated around a vertical axis so that protoconid and metaconid tips are aligned; right, vertical section running through both protoconid and metaconid EDJ tips, and an example of a thickness measure. (Andrews and Martin, 1991). In that case of an Ouranopithecus molar, the mesial-most section of Smith et al (2003), at an unstated distance from the initial section of Andrews and Martin (1991), exhibited a more salient EDJ cusp profile and a smaller enamel thickness value, indicating that the initially measured cross section was considerably off from the MCS.…”
Section: Measurements and Methodological Considerations Problem Of Sementioning
confidence: 99%
See 1 more Smart Citation
“…(c) Left, horizontal section after the entire volume data set of (b) was rotated around a vertical axis so that protoconid and metaconid tips are aligned; right, vertical section running through both protoconid and metaconid EDJ tips, and an example of a thickness measure. (Andrews and Martin, 1991). In that case of an Ouranopithecus molar, the mesial-most section of Smith et al (2003), at an unstated distance from the initial section of Andrews and Martin (1991), exhibited a more salient EDJ cusp profile and a smaller enamel thickness value, indicating that the initially measured cross section was considerably off from the MCS.…”
Section: Measurements and Methodological Considerations Problem Of Sementioning
confidence: 99%
“…(Andrews and Martin, 1991). In that case of an Ouranopithecus molar, the mesial-most section of Smith et al (2003), at an unstated distance from the initial section of Andrews and Martin (1991), exhibited a more salient EDJ cusp profile and a smaller enamel thickness value, indicating that the initially measured cross section was considerably off from the MCS. Similarly, we recently examined the measured block faces of an Australopithecus robustus molar sectioned by Grine and Martin (1988).…”
Section: Measurements and Methodological Considerations Problem Of Sementioning
confidence: 99%
“…Reported hominoid values from a controlled (physical) plane of section have necessarily been based on small sample sizes (Gantt, 1977;Martin, 1983Martin, , 1985Grine and Martin, 1988;Andrews and Martin, 1991;Macho, 1994;Beynon et al, 1998;Shellis et al, 1998;Grine, 2002;Olejniczak and Martin, 2002;Schwartz et al, 2003;Smith et al, 2003bSmith et al, , 2004Grine, 2005). Previous studies of extant ape molars have produced a maximum reported sample of 17 teeth from seven individuals of a single species (Martin, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…5,24,36,37 Finally, these results are considered in light of recent studies of enamel thickness within fossil and extant Homo sapiens, 35,[38][39][40] which are known to show a similar pattern of dental reduction over the same period. Given the significance of enamel thickness in assessments of hominoid systematics 28,29,32,35,41 and dental functional morphology, 33,34,42,43 characterization of enamel thickness within a geographically and temporally diverse hominoid genus will also permit more refined comparisons of limited samples of other fossil apes and humans.…”
Section: Introductionmentioning
confidence: 99%